Keterlibatan Amerika Serikat dalam Perang Vietnam: Faktor Ideologi, Identitas, dan Idealisme - Demas Nauvarian (Jurnal Hubungan Internasional, 2019)
This paper aims to prove the justification of US democracy in itsconsistency in the Vietnam War for two decades (1955-1975). This wasdone using the content analysis method of the US Department of Defense’sforeign policy documents in Vietnam - the Pentagon Papers - which werethe primary documents related to the process of making US foreign policyduring the Vietnam War. This was later matched with the view of DemocraticPeace Theory (Democratic Peace Theory) which has been widelyargued as the basis for policy making in the proxy war in the Cold Warera. This paper concludes that there are various other considerations,both rational and irrational factors, which were used by the United Statesin the Vietnam War